2021
DOI: 10.1002/er.7512
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed‐UV illumination on graphene oxide: A new strategy in photocatalytic synthesis of electrocatalysts to control the structural and electrochemical properties

Abstract: Summary This study demonstrated the capability of a novel method in controlling the structural and electrochemical properties of electrocatalysts, utilizing a pulsed‐ultraviolet (UV) setup for the synthesis procedure. A hand‐made reactor provided a new set of parameters. The variation of UVon and UVoff periods resulted in samples with a range of different structures, compositions, and activities. Graphene/Pt was prepared with varying forms of illumination pulse, and its hydrogen oxidation and oxygen reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Based on a study conducted by Wang et al, metal ions, M + , could be attracted to negatively charged GO sheets and cause partial neutralization of GO (eq ). false[ GO false] x + x normalM + GOM x However, methanol (as an organic hole scavenger) and water molecules tend to form hydrogen bonds with GO functional groups. The probability of forming a hydrogen bond between water molecules and GO is much more than forming the bond between the methanol molecule and GO, especially when the GO has already been stored in aqueous solutions …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on a study conducted by Wang et al, metal ions, M + , could be attracted to negatively charged GO sheets and cause partial neutralization of GO (eq ). false[ GO false] x + x normalM + GOM x However, methanol (as an organic hole scavenger) and water molecules tend to form hydrogen bonds with GO functional groups. The probability of forming a hydrogen bond between water molecules and GO is much more than forming the bond between the methanol molecule and GO, especially when the GO has already been stored in aqueous solutions …”
Section: Resultsmentioning
confidence: 99%
“…To assess the number of active sites for the hydrogen oxidation reaction, HOR, CV experiments were conducted (Figure ). Results from previous investigations have shown that the current approach produces Pt ions with a very high deposition efficiency and stability. ,, Based on those results, the ECSA and ORR performance were calculated with respect to 20 wt % Pt loading. The most promising electrochemical activity was for the sample prepared with a high concentration of Co 2+ , with the ECSA value of 191 m 2 ·g –1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations